Alinhamento das pesquisas de pós-graduação da Universidade Federal de Uberlândia com os Objetivos de Desenvolvimento Sustentável: Uma avaliação mediada por Inteligência Artificial. - Ribeiro, Helena Farias (2024)
ABSTRACT: Context: The relevance of the Agenda 2030 has grown in discussions involving society, organizations, and governments. Aware of the role played by Higher Education Institutions in promoting critical thinking towards sustainability, this study is conducted at the Federal University of Uberlândia (UFU), adopting the perspective of systems theory. Objective: The main objective of this work was to identify how the postgraduate research at UFU (Federal University of Uberlândia) contributes to the Sustainable Development Goals (SDGs). Although directly linked to SDG 4 (Quality Education), the study sought to understand the contribution of the Higher Education Institution to other SDGs. Method: This is a descriptive study as it focuses on the detailed description of characteristics, behaviors, patterns, or phenomena in a specific population or particular situation and has a quantitative nature. Additionally, this study utilizes secondary data, making the analysis documentary. The data were obtained through a sample of dissertations and theses conducted at UFU since 2015. Two analyses of the works were conducted: a "supervised" analysis performed by humans, classifying them based on alignment with the Sustainable Development Goals (SDGs), and an "unsupervised" analysis carried out using Artificial Intelligence (AI), applying topic modeling to the abstracts of these works to generate topics representing the database, which could be compared with the human analysis. Results: The analysis of 2563 works revealed the predominance of SDGs 3, 4, 9, 8, and 2, related to health, education, innovation, economic growth, decent work, sustainable agriculture, and zero hunger, respectively. Topic modeling confirmed the most frequent SDGs but also highlighted a gap in relation to other SDGs, indicating the need for future studies. Alignment with PPGAdm Concentration Area (Regionality and Management) and Research Line: The research aligns with the concentration area of the PPGAdm, emphasizing the importance of regionality in contributing to the Agenda 2030, as the goals are global, but the contribution is regional. Its inclusion in the research line is supported by the emphasis on the relationship between higher education institutions, regional development, and sustainability. Impact and Innovative Character in Intellectual Production: The research contributes theoretically by highlighting regional importance in achieving SDGs, presenting an innovative approach using AI to analyze the alignment of postgraduate research with Agenda 2030. Economic, Social, and Regional Impact: This work contributed by providing information about the Sustainable Development Goals (SDGs) in postgraduate research, indicating which SDGs need to be further explored in different areas of study. Additionally, this study generated a technical product, a dashboard containing charts illustrating the alignment of postgraduate research at UFU. The construction and additional details of the product are published in a technical report and presented in Appendix A (Soares et al., 2023; UFU SDG Panel, n.d.). Regional Implications: The research offers significant contributions to the regions influenced by UFU, emphasizing the importance of higher education in promoting regional sustainability. It also indicates research gaps related to Agenda 2030, where the University can contribute in the future. Sustainable Development Goals Addressed in the Research: Considering the UN Agenda 2030, the research primarily addresses SDGs 3, 4, 9, 8, and 2.